THE INFLUENCE OF TOP MANAGEMENT DEMOGRAPHIC CHARACTERISTICS ON DECISION MAKING APPROACHES - Ivana Bulog (Ekonomski Vjesnik, 2016)
Today’s organizational environment requires managers to be an excellent decision maker with the ability to make effective decisions which will shape business performance. Because of the role that managers have in today’s business settings, research interest in the relationship between individual characteristics and managerial decision making in all its aspects has increased over the last decade. This paper aims to provide an overview and discussion of how individuals make choices and decisions by examining the influence of top management demographic characteristics on decision making approaches. Findings suggest that demographic characteristics appear to be valuable for predicting which decision making approach managers prefer. The results of the study show that the average age and education level of decision makers is positively related to the rational decision making approach and negatively to the intuitive decision making approach. Tenure is positively related to the intuitive decision making approach, but the influence is not statistically significant. Also, a difference in the decision making approach was found with respect to gender. In light of the research findings, implications and limitations were discussed and some possibilities for future research are suggested.